1997
DOI: 10.1111/j.1469-7793.1997.693bj.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of motor units in human flexor digitorum profundus under different proprioceptive conditions

Abstract: Changing the posture of the human fingers can functionally ‘disengage’ the deep finger flexor muscle from its normal action on the terminal phalanx of the fourth (or third) finger. This enables the activity of the muscle to be studied both with and without its normal proprioceptive inputs. Spike trains of long duration from pairs of concurrently active motor units in this muscle were recorded in both the engaged and disengaged hand postures. Subjects voluntarily kept one of the motor units (the ‘controlled’ un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…Muscle spindles and GTOs are found in most muscles in the body, with the exception of the facial muscles (Folkins et al 1978;Lovell et al 1977). The involvement of the proprioceptive feedback in the modulation of motor units firings was previously suggested by Garland and Miles (1997) to explain their observation that the degree of cross-correlation among firing rates in the flexor digitorum profundus muscle varied when the fourth hand digit was flexed. They suggested that the altered proprioceptive feedback was either directly or indirectly involved, but did not provide evidence to substantiate the suggestion.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Muscle spindles and GTOs are found in most muscles in the body, with the exception of the facial muscles (Folkins et al 1978;Lovell et al 1977). The involvement of the proprioceptive feedback in the modulation of motor units firings was previously suggested by Garland and Miles (1997) to explain their observation that the degree of cross-correlation among firing rates in the flexor digitorum profundus muscle varied when the fourth hand digit was flexed. They suggested that the altered proprioceptive feedback was either directly or indirectly involved, but did not provide evidence to substantiate the suggestion.…”
Section: Discussionmentioning
confidence: 92%
“…It is also altered by different proprioceptive conditions (Garland and Miles 1997), exercise (Semmler and Nordstrom 1997), and aging (Erim et al 1999). It is unclear why these variations occur.…”
Section: Introductionmentioning
confidence: 99%
“…Although deafferented subjects may preserve some capacity for coarse repetitive movements [ 16-1 81, they have impaired ability to exert a constant force [9] or to reproduce fine manipulations. Poor recovery of muscle sensory function [ 171 may be an important determinant of the variable and limited recovery of muscle function after nerve injury [8].…”
Section: Introductionmentioning
confidence: 99%
“…In the hand, more attention has been paid to the evaluation of tactile sensation [12] than to recovery of muscle sensory function [17J Moreover, hand movement has some unique features [9], and it is claimed (controversially) that hand proprioception depends most on skin receptors, with minimal contribution from muscle and joint [15].…”
Section: Introductionmentioning
confidence: 99%
“…Dozens of reports have since adopted this notion, including the following, among others: 1) within the same muscle (Garland and Miles 1997;Kamen and Roy 2000;Keen et al 2012;Laine and Bailey 2011;Mellor and Hodges 2005;Nordstrom et al 1990;Schmied et al 1993); 2) across synergistic muscles (Barry et al 2009;Bremner et al 1991a, b;Carr et al 1994;Gibbs et al 1997;Keen and Fuglevand 2004;McIsaac and Fuglevand 2007;Powers et al 1989;Winges and Santello 2004); 3) during tremor (Halliday et al 1999;Logigian et al 1988;Semmler and Nordstrom 1995); 4) in various neuromuscular pathologies (Baker et al 1992;Farmer et al 1990Farmer et al , 1993Kirkwood et al 1984;Mottram et al 2010;Schmied et al 1999); 5) during various muscle contraction paradigms, such as precision grip tasks (Hockensmith et al 2005;Huesler et al 2000;Kilner et al 2002;Santello and Fuglevand 2004;Winges et al 2006); 6) in exercise training (Boonstra et al 2009;Dartnall et al 2008Dartnall et al , 2011Griffin et al 2009;Mochizuki et al 2005;Schmied and Descarreaux 2010); and 7) during muscle fatigue (Boonstra et al 2008;Grönlund et al 2009;…”
mentioning
confidence: 99%